Optimization of Noninvasive Methods of DNA Collection for Genetic Testing [287]. (May 2015) - Shurshalina, Anna; Adelson, Martin; Qui, Ani; Stemmer, Shlomo M.
Abstract : INTRODUCTION: The new era of molecular diagnostics based on advanced DNA sequencing technologies opens possibilities for targeted genetic screening of high-risk populations. Biological samples collected in a noninvasive manner such as mouth and buccal cells can supply DNA for genetic testing. METHODS: A total of 110 volunteers participated in a study comparing different noninvasive methods of DNA collection (cotton-tipped swab, multiple cytology brushes, alcohol-containing mouthwash solution) and different times of specimen storage before extraction (same day, 2, 5, 7, and 14 days postcollection) for BRCA testing by next-generation sequencing. Volunteers were divided into two groups: mouthwash collection (n=60) and buccal swabs (n=50). For DNA extraction, we compared two extraction kits (Thermo GeneJET and Qiagen). Individual compliance, sufficient quantity and quality of collected DNA, and cost of each method were assessed. RESULTS: The average total DNA yield was found to be significantly higher in the mouthwash group (4, 185±1, 916.7 ng) in comparison with the cotton-tipped swab (95.1±81.4 ng), flocked brush (164.7±143.0 ng), and cytology brushes (1, 123.4±1, 281 ng). Mouthwash DNA collection was also the most cost-effective method. There was no significant difference in the DNA yield when samples were stored at room temperature for up to 14 days before extraction. CONCLUSION: Our results indicated that noninvasive methods of DNA collection can provide sufficient DNA yield and quality for genetic testing. Buccal cells collected using commercially available mouthwash provide the highest DNA yield and can be stored for up to 14 days without a significant decrease of genetic material quality.